2016
DOI: 10.18674/exacta.v9i1.1783
|View full text |Cite
|
Sign up to set email alerts
|

Otimização Da Extração De Compostos Fenólicos Da Casca De Manga (Tommy Atkins) Utilizando Processo Assistido Por Ultrassom

Abstract: <p>A casca de manga é considerada um resíduo da indústria de alimentos, rico em compostos fenólicos e o ultrassom tem se destacado entre as técnicas tradicionais na extração destes compostos. O principal objetivo deste trabalho é discutir os parâmetros que influenciam na extração de compostos fenólicos da casca de manga por ultrassom. Para esse fim, concentração de álcool etílico (30, 50 e 70%), temperatura (40, 50 e 60 °C) e tempo (30, 40 e 50 minutos) foram avaliados, por meio do planejamento de Box-Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Literature reports similar behaviors which corroborates the results assessed in this work. For example, the positive influence of high temperature, also observed by Silva et al, (2016) and Guerra et al, (2016), may be due the increase of solubility and diffusivity as well as, a decrease in the viscosity of the phenolic compounds. Both effects improve the mass transfer and accelerate the extraction rates.…”
Section: Characterization Of Compoundsmentioning
confidence: 68%
See 2 more Smart Citations
“…Literature reports similar behaviors which corroborates the results assessed in this work. For example, the positive influence of high temperature, also observed by Silva et al, (2016) and Guerra et al, (2016), may be due the increase of solubility and diffusivity as well as, a decrease in the viscosity of the phenolic compounds. Both effects improve the mass transfer and accelerate the extraction rates.…”
Section: Characterization Of Compoundsmentioning
confidence: 68%
“…Regarding the ethanol percentage, Silva et al, (2016) and Guerra et al, (2016) also found a maximum amount of polyphenols extracted using 50% (v v -1 ) however, with positive effect of this variable probably due the different range studied. Finally, the cited authors found a maximum yield of polyphenol of 1225.7 and 2125.31 mg GAE 100 g -1 , however, was adopted a concentration lower than this work (around 0.005 and 0.0025 g mL -1 , respectively).…”
Section: Characterization Of Compoundsmentioning
confidence: 94%
See 1 more Smart Citation
“…In relation to flavonoids, increased temperature had a positive influence. In another study, GUERRA et al (2016) verified that the optimum operating condition for obtaining phenolic compounds in Tommy atkins bark is at a temperature of 60°C. TABARAKI et al (2012) also reported that temperature influenced the extraction process; heat makes the cell wall more permeable, increasing the solubility of the compounds and the diffusion coefficient of the solvent.…”
Section: Resultsmentioning
confidence: 85%
“…In order to obtain a high content of phenolic compounds and soluble sugars, it was found that the linear effect of the time variable had a positive effect ( p < .05) in UAE. Studies of UAE realized by Dranca and Oroian (2016) and Guerra, Garcia, and Silva (2016) showed that the longer time, 15–45 min, and 30–60 min, increased the extraction of phenolic compounds from eggplant peel (~ 11%) and mango peel (~ 8%), respectively. For sugars, Polachini et al.…”
Section: Resultsmentioning
confidence: 99%